Communication Techniques for Persuasion of Students and Lecturers In Shaping Behavior - Nasiratunnisaa Mallappiang; Muharram Muharram (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
Many factors influence a student's success in the academic world. One of them is the role of the lecturer in providing direction or guidance on the problems experienced by students while on campus. Lecturers who act like this are called academic advisors. Lecturers in the formation of student behavior are strongly influenced by the ability of lecturers to communicate. Persuasive communication is an effective communication technique in shaping behavior because by using this communication, students can do something they want without feeling burdened and afraid. Forming behavior is an activity of communication and social interaction between lecturers and students to convey their knowledge in small and large groups. In learning activities, there are teaching techniques so that learning objectives can be achieved. Persuasive communication, in this case, is effective enough to influence or shape behavior.